ELT STUDENTS' BELIEFS ABOUT AND STRATEGY USE OF TRANSLATION - Nafiye Çiğdem Aktekin; Ayşegül Uysal Gliniecki (Informascope, 2015)
Although the significance of translation for foreign language teaching had gone unnoticed for decades, the general attitude towards translation has begun to alter, and translation has started playing a vital role in language learning process and aids learners to comprehend and produce the English language.  Nevertheless, solely a small number of studies have been devoted to the contribution of translation to language learning, specifically for the students in English Language Teaching (ELT) departments. Thus, this study aims to explore the role of translation in ELT students' English learning, notably regarding their learning beliefs and learning strategies about using translation in learning the language.           Key words: Translation, English Language Teaching, strategy use, beliefs